Non‐enteric infections, antibiotic use, and risk of development of functional gastrointestinal disorders. Issue 11 (24th August 2015) - Paula, H.; Grover, M.; Halder, S. L.; Locke, G. R.; Schleck, C. D.; Zinsmeister, A. R.; Talley, N. J.
Abstract Background Gastrointestinal infections are risk factors for irritable bowel syndrome (IBS) and functional dyspepsia (FD). We investigated whether non‐enteric infections and antibiotic exposure are also associated with the development of functional gastrointestinal disorders (FGIDs). Methods In a nested case–control study, random samples of Olmsted County, MN, were mailed valid self‐report questionnaires from 1988 through 1994, and then follow‐up questionnaires from 1995 through 2003. Survey responders who did not report any FGID symptoms at baseline, but then reported such symptoms in at least one subsequent survey, were classified as new‐onset cases. Age‐matched controls were individuals who did not have symptoms at either the initial or subsequent surveys. Key Results The overall response rate was 78% to the initial survey and 52% to the follow‐up survey. Based on the responses, 316 participants had a new onset of an FGID (43 IBS constipation, 95 IBS diarrhea, 25 IBS mixed, and 153 other FGIDs, including FD) and 250 did not (controls). Around 76% (241/316) of cases reported a non‐enteric infection vs 66% (166/250) of the controls. The frequency of enteric infections was similar between the two groups. Of the new FGID cases, 83% had a non‐enteric infection that was treated with antibiotic. In a logistic regression model, treatment with antibiotics for a non‐gastrointestinal infection was associated with the development of an FGID (odds ratio = 1.90; 95% CI: 1.21–2.98; p = 0.005), after adjusting for age and sex. Conclusions & Inferences Based on a case–control study, treatment of a non‐gastrointestinal infection with antibiotics appears to be a risk factor for development of an FGID.